Epidemiology of pre-pregnancy body mass index (BMI) among mothers in Abu Dhabi, the United Arab Emirates - Taha, Zainab; Hassan, Ahmed Ali; Papandreou, Dimitrios (Frontiers in Global Women's Health, 2022)
Few studies have been conducted on prepregnancy body mass index (BMI) and its impact on pregnancy outcomes in the United Arab Emirates (UAE). Thus, the aim of this study was to investigate the prevalence and factors associated with underweight, overweight, and obesity among mothers with children under the age of two years in Abu Dhabi, the UAE. A cross-sectional multicenter study was conducted in 2017 and included data from seven government health care centers located in Abu Dhabi. Maternal prepregnancy BMI was calculated as the weight in kilograms (Kg) divided by the square of the height in metres (m) (kg/m2). A total of 1622 mother-child pairs were included in the current study. Out of 1622, 43(2.7%) were underweight, 1068(65.8%) were normal weight, 412 (25.4%) were overweight, and 99 (6.1%) were obese. Mothers with advanced maternal age (AMA) (≥ 30 years) were more likely to be overweight and obese. Mothers with less family income were more likely to be obese. Mothers with high birth order (≥ 2) were more likely to be overweight and obese and less likely to be underweight. Obese mothers were more likely to deliver via caesarean section (CS). All efforts should be directed to encourage all potential pregnant mothers, especially AMA, high birth order, and low family income, to maintain a healthy BMI before, during, and after delivery to achieve good pregnancy outcomes.